Targeting a transcription factor NF-κB by green tea catechins using in silico and in vitro studies in pancreatic cancer - Suhail, Mohd; Rehan, Mohd; Tarique, Mohammad; Tabrez, Shams; Husain, Amjad; Zughaibi, Torki A. (Frontiers in Nutrition, 2023)
Pancreatic cancer remains a lethal disease and a major public health problem globally. Nuclear factor-kappa B (NF-κB) has been identified as a therapeutic target in several cancers and plays an important role in inflammatory responses. Many phytochemicals, including catechins, have been reported in the scientific literature with efficient anticancer potential and minimal side effects. This study aims to gain insights into the inhibitory mechanism of catechin derivatives epicatechin (EC), epigallocatechin (EGC), epicatechin gallate (ECG), and epigallocatechin gallate (EGCG) using in silico and in vitro studies especially considering NF-κB targeting. We explored the binding pose, interacting residues and molecular interactions for catechin derivatives with NF-κB. Docking analysis showed that the catechin derivatives acted as covalent inhibitors with the p65 subunit of NF-κB and interacted with other residues through non-bonding interactions and hydrogen bonds. Further, we validated the effect of EGCG on NF-κB activity in pancreatic cancer cell lines MIAPaCa-2 and SU 86.86. Our in vitro data showed EGCG effectively reduced cell growth and proliferation, induced apoptosis, and inhibited NF-κB activity in the studied cell lines. In addition, EGCG repressed the expression of NF-κB target genes including MMP9, MMP2, cMyc, and BCL-2. Thus, targeting NF-κB with EGCG could be a potential therapeutic alternative for pancreatic cancer treatment.